Foreign trade in Alfonsín years: reflections from Argentina's trade balance (1983-1989) - Andrés Rossi, Ignacio (2023)
We review trade balance statistics in the years of Raúl Alfonsín (1983-1989), seeking to contribute to the discussion of trade policy on issues such as the origins of Mercosur (Southern Common Market) and the role of the US and European nations in the post-dictatorship. Through statistical sources in the Center for International Economics of the Secretariat of International Economic Relations, we analyze commercial links with different nation blocs, focusing on exports, imports, amounts reached, and product types that characterized the years of the recent democracy. In addition to the preponderance of the United States and Brazil as main trading partners, other countries, mainly European, had significant interference in Argentina's international trade. Thus, the origins of Mercosur and the growing hegemonic advance with the US are underestimated at this time by the European role in the trade balance.